CORAL REEF FISHES IN THE COASTAL WATERS OF SOUTH-CENTRAL VIETNAM - Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2009)
Studies on coral reef fishes in the coastal waters of South Central Vietnam were conducted at 42 sites of coral reefs at the four major locations of Van Phong Bay, Nha Trang Bay, Ninh Hai - Ninh Thuan and Ca Na Bay from 2006 - 2007, and combined with available  data  of  species  composition  from  previous  studies.  A  total  of  578  species representing 180 genera and 40 families of coral reef fishes was recorded. The analysis and comparison  indicate  that  diversity  of  coral  reef  fish  fauna  in  the  coastal  waters  of  South Central Vietnam was higher than that in other locations in the coastal waters of Vietnam (the Tonkin Gulf, southeastern and southwestern waters of Vietnam), more or less similar to that in the Spratly Islands and many other locations around the world. In the coastal waters of South Central Vietnam, Nha Trang Bay supported a higher diversity and abundance of most of fish families than Van Phong Bay, Ninh Hai - Ninh Thuan and Ca Na Bay.